Tinjauan Hukum terhadap Kebijakan Pemutihan Pajak Kendaraan Bermotor: Antara Kepentingan PAD dan Kepatuhan Wajib Pajak - Tedy Irawan; Adinda Berliana Rizkita Anjani; Diah Ajeng Pangestu; Marsya Amalina Djatmiko (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to review the legal aspects and impacts of the vehicle tax amnesty policy on increasing Regional Original Income or PAD due to late payment of vehicle tax, which has become one of the strategies adopted by local governments to optimize tax revenues and maintain the validity of vehicle data. This study uses normative juridical as its approach to review laws and regulations and uses relevant literature studies. The results of the study reveal that normatively, this policy has a strong legal basis and has been empirically proven to be able to increase tax revenues in the short term. However, there is a potential for a long-term decline if the policy is not accompanied by adequate supervision and education. Therefore, harmonious, transparent implementation and increased socialization are needed to avoid taxpayer misunderstandings. This study contributes to the understanding of the importance of balance between fiscal incentives and the powerlessness of regional tax governance.